Propriétés Antifongiques Des Légumineuses Médicinales De Côte d’Ivoire : Cas De Crotalaria retusa L. (Fabaceae) Sur La Croissance in vitro De Phytophthora sp. Et Fusarium solani, Deux Champignons Phytopathogènes - Dabé, Doga; Noël, Zirihi Guédé; Adolphe, Zézé (European Scientific Journal, ESJ, 2017)
The high cost of fungicides, the international markets standards for agricultural product quality, the environmental issues and consumer health discourage to the application of chemical control. The strategy is therefore to develop alternative solutions, less expensive and addresses environmental concerns. This study was conducted to evaluate the fungicidal potency of Crotalaria retusa L. on Phytophthora sp. and Fusarium solani, two phytopathogenic fungi. This plant was selected after an ethnobotanical study conducted in the sub-prefecture of Lauzoua in Côte d’Ivoire. It is considered to be the most widely used in the treatment of microbial diseases. The phytochemical screening of this legume species was carried out, and showed the presence of saponosides, sterols, tannins, alkaloids, flavonoids, polyphenols, quinones and polyterpenes. The sensitivity of these two phytopathogenic fungi strains was tested in vitro in presence of the aqueous extract of Crotalaria retusa L. by using double dilution method on PDA medium (Potato Dextrose Agar). The minimum inhibitory concentration (MIC) of spawn growth was 1.56 mg/ml for both fungi. The minimum fungicide concentration (CMF) was 6.25 mg/ml for Phytophthora sp and 12.50 mg/ml for Fusarium solani. The presence of chemical compounds in this plant justifies its antifungal activity and its traditional use areas.